2013
DOI: 10.1590/s0100-72032013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da postura corporal em mulheres com câncer de mama

Abstract: Postural changes were correlated with the type and side of surgery. The follow-up of this group after completion of treatment is needed to clarify long-term postural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 10 publications
1
17
0
7
Order By: Relevance
“…Table 2 presents the main methodological information of included studies. Although the methodology practically differs in all studies, the feet positioning was assembled in groups and the most common were: with inferior members in parallel and separated by a previously determined distance (Barbosa, Amorin, Zandonade, & Delaprane, 2013;Belli, et al, 2009;Iunes, Cecílio, Dozza, & Almeida, 2010;Iunes et al, 2005;Milanesi et al, 2011;Pezzan, João, Ribeiro, & Manfio, 2011;Sacco et al, 2007;Sacco et al, 2012;Tavares et al, 2013); with the inferior members positioned together (Chiao Yi, Jardim, Inoue, & Pignatari, 2008;Futlanetto, Chaise, Candotti, & Loss, 2011;Furlanetto et al, 2012;Munhoz, Marquez, & Siqueira, 2005); with the individual standing in self-referred or usual posture (Fedorak, Ashworth, Marshall, & Paul, 2003;Gadotti & Biasotto-Gonzalez, 2010;Gadotti, Armijo-Olivo, Silveira, & Magee, 2013;Raine & Towmey, 1994a;Raine & Towmey, 1994b;Salazadeh et al, 2014;Yu Cho, 2007); and standardizing the individual usual posture by using the strategy of outlining the supporting base of each person to utilize as a mold for the photos (Coelho et al, 2013;Coelho et al, 2014;de Almeida et al, 2013;Dunk, Lalonde, & Callaghan, 2005;Ferreira, Duarte, Maldonado, Bersanett, & Marques, 2011;Figueiredo, Amaral, & Shimano, 2012;Glaner, Mota, Viana, & Santos, 2012;Lopes et al, 2014;Miranda, Schor, & Girão, 2009;Pachioni et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents the main methodological information of included studies. Although the methodology practically differs in all studies, the feet positioning was assembled in groups and the most common were: with inferior members in parallel and separated by a previously determined distance (Barbosa, Amorin, Zandonade, & Delaprane, 2013;Belli, et al, 2009;Iunes, Cecílio, Dozza, & Almeida, 2010;Iunes et al, 2005;Milanesi et al, 2011;Pezzan, João, Ribeiro, & Manfio, 2011;Sacco et al, 2007;Sacco et al, 2012;Tavares et al, 2013); with the inferior members positioned together (Chiao Yi, Jardim, Inoue, & Pignatari, 2008;Futlanetto, Chaise, Candotti, & Loss, 2011;Furlanetto et al, 2012;Munhoz, Marquez, & Siqueira, 2005); with the individual standing in self-referred or usual posture (Fedorak, Ashworth, Marshall, & Paul, 2003;Gadotti & Biasotto-Gonzalez, 2010;Gadotti, Armijo-Olivo, Silveira, & Magee, 2013;Raine & Towmey, 1994a;Raine & Towmey, 1994b;Salazadeh et al, 2014;Yu Cho, 2007); and standardizing the individual usual posture by using the strategy of outlining the supporting base of each person to utilize as a mold for the photos (Coelho et al, 2013;Coelho et al, 2014;de Almeida et al, 2013;Dunk, Lalonde, & Callaghan, 2005;Ferreira, Duarte, Maldonado, Bersanett, & Marques, 2011;Figueiredo, Amaral, & Shimano, 2012;Glaner, Mota, Viana, & Santos, 2012;Lopes et al, 2014;Miranda, Schor, & Girão, 2009;Pachioni et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…Another well-established pattern of foot positioning utilizes the lower limbs positioned in parallel and apart (Barbosa et al, 2013;Belli et al, 2009;Iunes et al, 2005;Iunes et al, 2010;Milanesi et al, 2011;Pezzan et al, 2011;Sacco et al, 2007;Sacco et al, 2012;Tavares et al, 2013). One example of protocol that utilizes that type of position for photogrammetry is the classical study by Kendall et al (1995) which believes that postural evaluation should be conducted with a supporting base with the individual's feet in parallel, their heels separated by a 7.5cm distance and the hind feet abducted 8º to 10º from the median line.…”
Section: Raine (1994)mentioning
confidence: 99%
“…Numerous authors showed in their publications that after a one-side mastectomy, previously symmetrical body structure changes, which may be connected to changes in the parameters characterizing body posture. Breast weight influences the body's gravity center location and removal of one of them thereby causes changes in body posture (elevated shoulders and one-axis trunk inclination) [23,24]. Incorrect body posture may, in turn, result in other somatic changes, while pain and limited mobility of the upper limb causes alterations of body statics [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The camera was positioned on a tripod at a distance of 4m, and this evaluation was performed by a qualified physiotherapist. (21) h) Biophotogrammetry was used in 1 study: Barbosa et al (32) . The images were acquired with the use of a camera positioned on a tripod with 1m tall.…”
Section: Discussionmentioning
confidence: 99%
“…For image processing was used CorelDraw® Software. (32) i) Evaluation sheet-observation was used in 1 study: Colpo et al (34) .…”
Section: Discussionmentioning
confidence: 99%